Acute Respiratory Distress Syndrome and Risk of AKI among Critically Ill Patients - Darmon, Michael (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Increasing experimental evidence suggests that acute respiratory distress syndrome (ARDS) may promote AKI. The primary objective of this study was to assess ARDS as a risk factor for AKI in critically ill patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This was an observational study on a prospective database fed by 18 intensive care units (ICUs). Patients with ICU stays >24 hours were enrolled over a 14-year period. ARDS was defined using the Berlin criteria and AKI was defined using the Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease criteria. Patients with AKI before ARDS onset were excluded. RESULTS: This study enrolled 8029 patients, including 1879 patients with ARDS. AKI occurred in 31.3% of patients and was more common in patients with ARDS (44.3% versus 27.4% in patients without ARDS; P<0.001). After adjustment for confounders, both mechanical ventilation without ARDS (odds ratio [OR], 4.34; 95% confidence interval [95% CI], 3.71 to 5.10) and ARDS (OR, 11.01; 95% CI, 6.83 to 17.73) were independently associated with AKI. Hospital mortality was 14.2% (n=1140) and was higher in patients with ARDS (27.9% versus 10.0% in patients without ARDS; P<0.001) and in patients with AKI (27.6% versus 8.1% in those without AKI; P<0.001). AKI was associated with higher mortality in patients with ARDS (42.3% versus 20.2%; P<0.001). CONCLUSIONS: ARDS was independently associated with AKI. This study suggests that ARDS should be considered as a risk factor for AKI in critically ill patients.